The principle of insignificance in crimes against the tax law (Revista da Faculdade de Direito, Universidade de São Paulo, 2012)
The Principle of Insignificance, which addresses the Magistrate derives from the Principle of Minimum Intervention of the State, which is addressed to the legislator. This is not a species of the genus Theory of Social Adjustment, when the conduct is not typed, given its social acceptance. In a wrongful conduct that meets formally and materially the offense, it will be up to the magistrate feature restrictive interpretation, making the atypical behavior, where the slightest injury to legally protected. The atypicality is given by the Principle of Insignificance. Having no legal provision, becomes the erroneous reasoning of the magistrate’s application when there is legal provision establishing values for non-criminal deserving of dignity, as in Tax Law. In such cases, will occur mere standardized service. Its applicability in spite of nonlegislative forecast does not entail legal uncertainty, given the slightest injury.